الاشتقاق الإنجازي في شرح الاستراباذي على كافية ابن الحاجب - دالة الاستفهام نموذجا. - هجيرة, كحلة; لزهر, كرشو (جامعة الوادي - University of Eloued, 2023)
ملخص: يتأسس هذا المقال على دعوى مفادها أن نظرية الاشتقاق الإنجازي، والتي نظر لها كل من سيرل وانسكومبر وريكاناتي لها أصول في الممارسة التراثية في العديد من قطاعاتها المعرفية كالنحو، البلاغة، التفسير ... وباعتبار الاستراباذي واحدا من النحاة الأفذاذ، فإن له إسهامات مذكورة في هذا المجال تنظيرا وتطبيقا لاهتمامه بالأفعال الإنجازية المشتقة، وكيفية اشتقاقها انطلاقا من أفعال إنجازية مباشرة، معروضة في الخطاب، باعتماد مؤشرات اشتقاقية أو ملابسات الإنجاز أو معارف مشتركة. وبعد دراسة عينات من مدونة "شرح الكافية" وتحليل المحتويات، والاستدلال على الفرضيات الموضوعة، توصلت الدراسة إلى نتيجة هامة: وهي ثبوت تلك الفرضيات واستجابة مدونة الرضي لمقومات نظرية الاشتقاق الإنجازي محققة لأهدافها كما يصفها المنظرون المعاصرون. الكلمات المفتاحية: الاشتقاق الإنجازي،مؤشرات اشتقاقية، ملابسات الإنجاز، معارف مشتركة. ABSTRACT : This article is based on the hypothesis that the theory of Achievement derivation based of the works of François Recanati and JC. Anscombre,it has its roots in the traditional practice in many of its knowledgeable sectors like grammar,figurative language, Explanation…. Considering Al Istrabadi as one of most highly regarded grammarianswhose contributions are mentioned in this disciplinewhether its theory and application because of his interest in the derived verbs of achievement, and how to derive it form direct achievement verbs displayed in speech, by applying derivative indications or circumstancesof achievement or shared knowledge. And after studying samples of " Sharh Al Kafiat"and analyzing the components , and Inference of the established hypotheses , the study come to an important conclusion : the standing of those hypotheses and the compatibility of the writings of Al Radhifor the requirements for The derivative theory of achievement accomplishing its objectives as the modern theorists describe it. Keywords:
مقال
Keywords: لاشتقاق الإنجازي ; مؤشرات اشتقاقية ; ملابسات الإنجاز ; معارف مشتركة; Derivative achievement, Derivative indications, Circumstances of achievement ,Shared Knowledge.